PROFIL PENGOBATAN PASIEN DIABETES MELLITUS TIPE 2 DI INSTALASI RAWAT INAP RSUD UNDATA PALU TAHUN 2012 - Yulianti, Sri Rahayu; Mukaddas, Alwiyah; Faustine, Inggrid (Natural Science: Journal of Science and Technology, 2014)
Diabetes mellitus (DM) is a metabolic disease prevalence increasing year by year. DM disease characterized by hyperglikemia that caused by abnormalities of insulin secretion, insulin activity or both. DM consists of two main types, namely DM type 1 and type 2. This research aims to know the profile of the treatment of type 2 DM in Undata hospital using method a retrospective medical record by noting that in accordance with the criteria of inclusion and exclusion. Among 147 population, 69 was taken as samples, then its characteristic were described based on each variable, resulting in a frequency distribution and proportion of each variable. The results showed that the most common therapy for type 2 DM was rapid acting insulin (novorapid), and the most common used of oral antidiabetic was metformin, and is most often treatment was combination of metformin and glimepirid.